Constitutionalism, legitimacy, and power : nineteenth-century experiences - Grotke, Kelly L; Prutsch, Markus Josef, 1981- (Oxford : Oxford University Press, 2014)
Critically analysing 19th century constitutions in tandem with the political and social circumstances of their creation, enactment, and stated objectives, this book explicitly counters any simplistic narratives asserting that constitutions offer a straightforward, law-based path to increasing democracy, equality and liberty.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on October 28, 2014).
Keywords: Constitutions -- History -- 19th century